Symptomatic Thrombocytopenia from Apixaban in Patient with Deep Vein Thrombosis: A Case Report - Pinzon, Rizaldy Taslim; Sari, Efrilia (Acta Neurologica Indonesia, 2025)
Introduction: The Non-Vitamin K Antagonist Oral Anticoagulants (NOACs) is the main treatment of venous thrombosis. A review of use for rare adverse reaction of these drugs are still needed. The use of Apixaban related thrombocytopenia has been reported previously, but its clinical significance remains still under-reported. We report a case of 63-year-old Asian woman who suffered from severe and symptomatic thrombocytopenia with mild bleeding manifestation after taking Apixaban. Case Report: A 63‐year‐old Asian woman was admitted for neurological clinical due to severe asthenia for 1 week ago accompanied by multiple ecchymoses. The initial presentation was left arm and leg oedema. This patient was previously treated with Apixaban, Furosemide, Vitamin D, and Metamizole for deep vein thrombosis in the femoral, popliteal, and subclavian veins. Apixaban had been used by the patient for 2 months at a dose of 5 mg per day. The test results showed that the patient had mild anemia and a significantly low platelet count. Discussion Potential mechanisms of Apixaban-induced thrombocytopenia may involve immune-mediated reactions through drug-dependent antibodies, or bone marrow suppression pathway. This rapid increase in platelet count supports the immune-mediated hypothesis, as bone marrow recovery generally takes more than 7 days. Conclusion: We report on a patient who developed severe and symptomatic thrombocytopenia due to Apixaban. The other possible causes of thrombocytopenia were ruled out.Keywords: apixaban; thrombocytopenia-induced; NOAC